English Result. Elementary: Photocopiable Resource Book - Tabor C. Carol (Oxford, Oxford University Press, 2012)
There are 48 Photocopiable Activities - one for every main Student's Book lesson. They are designed to consolidate the material covered in the Student's Book lesson in an engaging and communicative way. Most of the activities provide practice in the grammar or vocabulary of the lesson, and all give your students the opportunity to describe, explain, speculate, debate, and question in English. The Teacher's Notes provide full guidance in using the activities as well as all the answers. There are 18 Photocopiable Worksheets to use with the Student's DVD in class. They allow you to fully exploit the documentary clips and authentic interviews with your students. The Teacher's Notes provide step-by-step instructions and answers.